Fluorenyl-Schiff-base ligands and their dicopper(II) complexes. Synthesis, structural and spectroscopic characterization and DNA binding assays. (1st April 2018) - dos Santos Carlos, Fabiane; Nunes, Marcelo Carpes; Iglesias, Bernardo Almeida; Zambiazi, Priscilla J.; Hörner, Manfredo; de Moraes, Guilherme A.; Machado, Guilherme Sippel; Ribeiro, Ronny Rocha; Nunes, Fábio Souza
Graphical abstract: Synthesis and a comprehensive chemical investigation of ligands L1, L2 and their dicopper(II) complexes was performed by elemental analysis, single X-ray diffractometry, ESI-MS, 1 H and 13 C NMR, FTIR, EPR, UV–Vis and emission spectroscopies. Abstract: Schiff-base ligands L1 and L2 containing fluorene as fluorophore were synthesized thorough condensation of salicylaldehyde and 2, 6-diformyl 4-methylphenol with 6-(9-fluorenyl)-1, 4, 8, 11-tetraazaundecane-5, 7-dione, respectively. A comprehensive spectroscopic analysis was performed by elemental analysis, ESI-MS, 1 H and 13 C NMR, FTIR, EPR, UV–Vis and emission spectroscopies. Ligand L1 binds copper(II) to form [Cu2 (L1)2 ]·2H2 O that crystallizes in orthorhombic system and space group P 21 /n . Assignments to the UV–Vis and EPR spectra allowed access to Jahn–Teller stabilization energies ( E JT ) at 6345 and 5435 cm −1 for complexes [Cu2 (L1)2 ]·2H2 O and [Cu2 (L2)](ClO4 )4 ·4H2 O, respectively, and to their corresponding spin orbit coupling constants λ = −428 and −398 cm −1 . The EPR spectrum of [Cu2 (L2)](ClO4 )4 ·4H2 O in the solid state showed a half-field Δ mS = ±2 transition, supporting the dicopper composition. The fluorenyl copper(II) derivatives demonstrated a moderate binding to ct-DNA than the fluorenyl-ligand molecule following the increasing order of ( K b ): L1 < [Cu2 (L1)2 ]·2H2 O < [Cu2 (L2)](ClO4 )4 ·4H2 O.